Depression in seizure disorder - Shakya, DR (Health Renaissance, 2012)
Depression, a psychiatric disorder is common and can present with various forms in seizures. Here is a seizure case with depression, as manifestation and as co-morbidity, presented to highlight the prevalence and management issues. A 35-year married female presented to a health-camp with unresponsive spells and depressive symptoms. For 5 years, she had altered consciousness spells associated with deviation of mouth and turning head to left and stiffening of right limbs, followed by GTCS every 15-90 days. The frequency increased in last 6 months. Her supportive mother-in-law died 12 months back and, she started worrying about her illness and family. Her sleep and appetite decreased. She frequently cried alone, more in 2-3 days after seizure spells, in last 7 months. She repeatedly expressed guilt and death wish, and once attempted hanging. Referral was made from the camp for hospital admission. After EEG report of ‘left temporal seizure’, mood stabilizing anti-epileptic and seizure friendly antidepressant were started with diagnosis of ‘Seizure and severe depression’. DOI: http://dx.doi.org/10.3126/hren.v10i1.6010 HREN 2012; 10(1): 59-61